A COMPARATIVE STUDY OF FLEXIBILITY OF PLAYERS OF KABADDI, KHO-KHO AND VOLLEYBALL OF GUJARAT STATE (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The Purpose was A Comparative Study Flexibility of Players of Kabaddi, Kho- Kho and Volleyball of Gujarat State. In the present study, 72 players of Kabaddi, 72 of Kho-Kho and 72 players of Volleyball participated at state level in Gujarat State were randomly selected of Vadodara, Bharuch and Surat. All selected players were of 13 to 17 years of age. The Flexibility for Floor touch test (Kraus Weber test) was measure of Marks Statistical technique such as analysis of variance was applied to know aspects of Flexibility of players of Kabaddi, Kho-Kho and volleyball of Gujarat State. Significance was examined at 0.05 levels by applying LSD Post Hoc Test to mean difference. F’ ratio of flexibility of male players of Kabaddi, Kho-Kho and volleyball of Gujarat State selected at state level was found 0.115, which was not follow significant at 0.05 levels. Equality was found in flexibility of players of all three groups. Flexibility plays an important role in sports so such results are attained in the study.